2012
DOI: 10.1016/j.vaccine.2012.01.070
|View full text |Cite
|
Sign up to set email alerts
|

Design considerations for liposomal vaccines: Influence of formulation parameters on antibody and cell-mediated immune responses to liposome associated antigens

Abstract: Liposomes (phospholipid bilayer vesicles) are versatile and robust delivery systems for induction of antibody and T lymphocyte responses to associated subunit antigens. In the last 15 years, liposome vaccine technology has matured and now several vaccines containing liposome-based adjuvants have been approved for human use or have reached late stages of clinical evaluation. Given the intensifying interest in liposome-based vaccines, it is important to understand precisely how liposomes interact with the immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
193
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 276 publications
(212 citation statements)
references
References 227 publications
6
193
0
3
Order By: Relevance
“…Various types of liposomes are used clinically as vehicles for drugs and vaccines [5]. Liposomes can be designed for multiple purposes, including immune modulation to enhance or inhibit a specific response [6].…”
mentioning
confidence: 99%
“…Various types of liposomes are used clinically as vehicles for drugs and vaccines [5]. Liposomes can be designed for multiple purposes, including immune modulation to enhance or inhibit a specific response [6].…”
mentioning
confidence: 99%
“…7 Nevertheless, anionic liposomes proved to be a potent adjuvant formulation platform when combined with a TLR4 agonist and the vaccine antigen. While some reports conclude that electrostatic or covalent antigen association with liposomes enhances vaccine potency, [20][21][22] other researchers have reported that simple mixtures of anionic liposomes with anionic vaccine antigens result in potent antibody and cellular immune responses, where significant antigen-liposome association was evident even though both components were anionic.…”
mentioning
confidence: 99%
“…Figure 6 showed the pattern of immune response against STa Regarding the stability of STa cationic nanoliposomes after storage for three months, there was non-statistically significant change in either the particle size, PDI or zeta potential values, suggesting the subtle retaining of their physicochemical properties during refrigeration storage. This stability might be attributed to the charged nature of the vesicles, which allowed the vesicles to resist aggregation and fusion [44,45] Furthermore, being in the range of +30 mV, the vesicular dispersions were considered to be adequately stable by creating sufficient repulsion between the particles [46]. efficiency of 12.56% ± 4.2, strongly suggested the electrostatic and physical incorporation of STa onto cationic lipids.…”
Section: Sta Antibody Binding Assaymentioning
confidence: 99%